The Credit System and Harmonisation of Higher Education in Ethiopia:: Implementation Practices and Challenges - Adamu, Abebaw Yirga (International Journal of African Higher Education, 2020)
This article analyses the implementation of a credit system and its contribution to the harmonisation of higher education in Ethiopia. Harmonisation has been used as a strategy to respond to the challenges of globalisation and internationalisation. A credit system is one of the tools to accomplish this objective. Harmonised academic policy, modularised curricula, and the introduction of the new credit system, the European Credit Accumulation and Transfer System are major initiatives that could contribute to the harmonisation of higher education in the country. The article identifies the factors that hinder this effort. The lack of clear policy directives on the use of the academic credit system negatively impacted implementation of the ECTS, calling for directives that clearly set out the details of a national academic credit system which should apply across higher education institutions, both public and private, and programmes at all levels.